2021
DOI: 10.1109/access.2021.3070650
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Method of Sink Node Path Planning Guided by the Hamiltonian of Quantum Annealing Algorithm

Abstract: In order to solve the NP-hard problem of mobile sink path planning in wireless sensor networks (WSN) where the communication range is modeled as a circular area and overlaps with each other, this paper proposes a sink node path planning method guided by the Hamiltonian of quantum annealing algorithm (EMGH) to balance the energy consumption of wireless sensor networks, improve the network life and solve the energy hole problem. First of all, this paper analyzes the problem in theory, and transforms the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It was discovered that 75 combinations of metrics and state-of-theart methods were mapped and compared out of which 60 (80%) stated that the QA performed better, 7 (9.33%) stated they have equivalent performance, and 8 (10.67%) showed that QA has lower performance. The most widely used stateof-the-art method for comparison was found to be simulated annealing as indicated by 21 (42%) of the 50 research which include [130], [149], [152], [154], [161], [168], [171], [189], [212], [217], [218], [223], [229], [238], [239], [242], [243], [246], [249], [251], [252]. This is due to the fact that QA is analogous to simulated annealing (classical approach) but in substitution of thermal activation by quantum tunneling.…”
Section: ) Results Reporting On Rq2mentioning
confidence: 99%
“…It was discovered that 75 combinations of metrics and state-of-theart methods were mapped and compared out of which 60 (80%) stated that the QA performed better, 7 (9.33%) stated they have equivalent performance, and 8 (10.67%) showed that QA has lower performance. The most widely used stateof-the-art method for comparison was found to be simulated annealing as indicated by 21 (42%) of the 50 research which include [130], [149], [152], [154], [161], [168], [171], [189], [212], [217], [218], [223], [229], [238], [239], [242], [243], [246], [249], [251], [252]. This is due to the fact that QA is analogous to simulated annealing (classical approach) but in substitution of thermal activation by quantum tunneling.…”
Section: ) Results Reporting On Rq2mentioning
confidence: 99%
“…The proposed method needs to be implemented with the help of commercially available quantum annealing hardware and a purely classical solver, "qbsolv" released by D-Wave. In [29], the mobile sink node collects data from all nodes within the communication range along the planned path and returns to the initial location after completing one round. The problem of finding the shortest path for a mobile sink node is essentially a traveling salesman problem (TSP).…”
Section: Related Workmentioning
confidence: 99%
“…Different from the simulated annealing algorithm which jumps over the barrier to eliminate the local optimum, the quantum annealing algorithm introduces a penetration field into the quantum system and generates quantum wave motion to penetrate the potential barrier itself, then reaches the lowest energy state [29]. In the early stage of annealing, the kinetic energy term is relatively large, providing a large disturbance that can fully traverse the entire solution space.…”
Section: Quantum Annealingmentioning
confidence: 99%
See 1 more Smart Citation